Bone and muscle development in three inbred female mouse strains - Föger-Samwald, Ursula; Papageorgiou, Maria; Wahl-Figlash, Katharina; Kerschan-Schindl, Katharina; Pietschmann, Peter (Osteologie, 2021)
Muscle force is thought to be one of the main determinants of bone development. Hence, peak muscle growth is expected to precede peak bone growth. In this study, we investigated muscle and bone development in female C57BL/6 J, DBA/2JRj, and C3H/HeOuJ mice. Femoral cortical and trabecular bone structure and the weights of selected muscles were assessed at the ages of 8, 16, and 24 weeks. Muscle mass increased from 8 to 24 weeks in all 3 strains, suggesting peak muscle development at 24 weeks or later. Bone volume fraction, trabecular number, and connectivity density of the femur decreased or remained unchanged, whereas trabecular density and trabecular thickness largely increased. These results suggest a peak in trabecular bone accrual at 8 weeks or earlier followed by further increases in density and structural reorganization of trabeculae. Cortical density, cortical thickness, and cortical cross sectional area increased over time, suggesting a peak in cortical bone accrual at 24 weeks or later. In conclusion, our data provide evidence that growth of muscle lags behind trabecular bone accrual.
Keywords: Bone microstructure; Inbred mouse strains; Peak bone mass; Peak muscle mass